Remnants of Colonialist Ideology in Patagonian Tourism Representations and How Collaborative Heritage Tourism Can become Inclusive Heritage. Issue 1 (1st December 2020) - Berg, Kimberly
Abstract: This paper explores the way in which colonial discourse is engaged and represented throughout the Argentinian Patagonian tourism industry and accompanying cultural heritage sites, as a resource from which local cultural communities gain political and social capital. Patagonian history is often associated with the presence of three distinct groups—the early Spanish colonial settlers, the indigenous groups, and the more contemporary Welsh diaspora. However, only the Welsh have been able to capitalize on this history. Regional history now commemorates and values Welsh presence over both predecessor groups. Despite this unequal valuing, however, Welsh heritage could conceivably be positioned as a tool for collaboration with that of indigenous heritage, in order to elevate this marginalized ethnic minority, and create a more inclusive heritage tourism destination. This paper explores the multiple cultural histories of the Patagonian landscape, through the lens of heritage representation, to argue how and why Welsh heritage is privileged, compared to its Patagonian counterparts, and the potential implications of the positioning of Welsh heritage for the Patagonian heritage industry more broadly.